Contrast-enhanced ultrasound findings of primary hepatic non-Hodgkin’s lymphoma: a case report - Tang, Can; Zhang, Heqing; Tian, Mei; Peng, Yulan (Frontiers in Oncology, 2024)
Primary hepatic lymphoma (PHL) is rare, and its early diagnosis is difficult. This article presents a primary hepatic non-Hodgkin's lymphoma (NHL) case report.A 52-year-old woman was admitted to the hospital due to a fever. After undergoing laboratory examination, contrast-enhanced computed tomography (CT), ultrasound, and contrast-enhanced ultrasound (CEUS), only CEUS suggested malignancy. Then, the patient underwent a laparoscopic liver biopsy, which diagnosed NHL. Previous studies have shown that hepatic lymphoma is a hypoglycemic tumor, and the enhanced CT and magnetic resonance imaging (MRI) scans are mostly mildly intensified. At the same time, the two-dimensional and color Doppler ultrasonography are mostly atypical. CEUS has unique advantages in displaying micro-vessels, which can be helpful in the diagnosis of primary hepatic lymphoma.